2016
DOI: 10.1007/s11356-016-6824-9
|View full text |Cite
|
Sign up to set email alerts
|

Illicit drugs and their metabolites in 36 rivers that drain into the Bohai Sea and north Yellow Sea, north China

Abstract: Illicit drugs and their metabolites have recently been recognized as an emerging group of contaminants due to their potential ecotoxicological impact in aquatic ecosystems. To date, information on the occurrence of these compounds in the aquatic environment of China remains limited. In this study, we collected surface water samples from 36 rivers in north China that discharge into the Bohai Sea and north Yellow Sea and measured the concentrations of amphetamine-like compounds, ketamines, cocainics, and opioids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…A number of WWTPs discharge their effluent to the Mgeni River and the concentration of pharmaceuticals, as expected, was higher than in the Msunduzi River. Environmental concentration levels obtained in this study were within range of the data from the literature [17,40,41,42].…”
Section: Resultssupporting
confidence: 83%
“…A number of WWTPs discharge their effluent to the Mgeni River and the concentration of pharmaceuticals, as expected, was higher than in the Msunduzi River. Environmental concentration levels obtained in this study were within range of the data from the literature [17,40,41,42].…”
Section: Resultssupporting
confidence: 83%
“…3 and Tables S13 and S14. Runoff data are referenced from previous reports (2016 ;Cui, 2008;Wang et al, 2016a). The riverine discharges of Si-PFASs were 20.3 t/y via the dissolved phase and 0.30 t/y via the particle phase.…”
Section: Riverine I-pfas Discharge Fluxesmentioning
confidence: 99%
“…In Huangpu River in Shanghai, caffeine, cotinine, and paraxanthine were detected with high detection frequency and concentrations, whereas the levels of other illicit drugs, such as pseudoephedrine, benzoylecgonine, and methadone, ranged from below the limit of detection (LOD) to several tens of ng L -1 (Yao et al, 2016). Wang et al (2016) found that METH and KET were the most abundant compounds in 36 rivers that are drained into the Bohai Sea and the north Yellow Sea. In 49 lakes and four major rivers (i.e., Yellow River, Songhua River, Pearl River, and Yangtze River) in China, the concentrations of METH, AMP, KET, and some other drugs were measured (Li et al, 2016).…”
Section: Introductionmentioning
confidence: 99%